Effects of Intensive Fattening With Total Mixed Rations on Carcass Characteristics, Meat Quality, and Meat Chemical Composition of Yak and Mechanism Based on Serum and Transcriptomic Profiles - Liu, Yi-Xuan; Ma, Xiao-Ming; Xiong, Lin; Wu, Xiao-Yun; Liang, Chun-Nian; Bao, Peng-Jia; Yu, Qun-Li; Yan, Ping (Frontiers in Veterinary Science, 2021)
The objective of this study was to investigate the effects of intensive fattening with total mixed rations (TMR) on the carcass characteristics, meat quality, and chemical composition of the yak meat. To provide theoretical data for evaluating the quality of yak meat during natural grazing and short-term fattening. In fattening yak, the carcass weight (CWT) was increased by 106.43% while the cooking loss, tenderness, and drop loss were significantly improved due to higher intramuscular fat content and lower moisture (P < 0.05). Protein, fat, calcium and amino acids were also much higher (P < 0.01) in fattening yak, as compared with the grazing yak. The levels of albumin (ALB), lactate dehydrogenase (LDH), triglyceride (TRIG), and amylase (AMYL) in serum indicated that fattening yaks were in better nutritional status. The transcriptomics analysis showed that the high expression of genes ACSL1 and ACACB improved the synthesis and deposition of fat in fattening yak, and the proteolysis was weakened by the regulation of SLC7A8, ATP1A4, ATP1A1, SLC3A2, and CPA3 gene expression. These results indicated that fattening with TMR improves the yield and quality of the yak meat.